We use the formula a^2 - b^2 = ( a - b )( a + b );
We have a = 5m - 2 and b = 3m - 4;
<span>(5m-2)^2-(3m-4)^2 = (5m - 2 -3m + 4) x (5m-2 + 3m - 4) = (2m + 2)(8m - 6) = 2(m +1) x 2(4m - 3) = 4(m+1)(4m-3);
</span>
Answer:
12.5
Step-by-step explanation:
5/2*5=12.5
Answer:
triangle
njjnkj
Step-by-step explanation:
Answer:
shopping for a car
Step-by-step explanation:
lets say you want to buy a new car, you ask yourself, hmm, which one is the best for me. or which car has the best milage. those type of things